Shedding of TNFR1 induced by protein A decreases TNF-alfa; availability and inflammation during systemic Staphylococcus aureus infection - Giai, Constanza (2013)
Staphylococcus aureus infections are an important concern in public health due to their increasing incidence and high rates of mortality. The S. aureus success as a pathogen is highly related to its enormous capacity to evade the host immune response. The critical role of TNF-alpha in the initial host defense against staphylococcal systemic infection has been demonstrated in experimental models and may partially explain the lack of significant benefits observed in clinical trials attempting to neutralize this cytokine in septic patients. S. aureus protein A plays a key role in regulating inflammation through its ability to bind and signal through the TNF-alpha receptor (TNFR1). In this study, we demonstrate that S. aureus, via protein A mediated signaling, induces early shedding of soluble TNFR1 which precedes the secretion of TNF-alpha in vitro and in vivo. The results obtained using a protein A deficient mutant and tnfr1-/- mice strongly suggest that the increased levels of soluble TNFR1 present during S. aureus experimental infection may neutralize circulating TNF-alpha and impair the host inflammatory response. Early shedding of soluble TNFR1 induced by protein A may constitute a novel mechanism by which S. aureus subverts the host immune response.